A reflexão interativa com instrumento de desenvolvimento profissional: um estudo com professores de inglês da escola pública - Rosane Rocha Pessoa (2002)
This qualitative study investigates the interactive reflection of four state school English teachers from Goiânia in the State of Goiás. Presupposing that not only eflection but also interaction are powerful instruments for teacher development, the objective was to examine the reflections of these four teachers on their pedagogical practice and its consequences for their students, as well as to verify if the interactivereflection about the classroom events promoted professional development. The theoretical framework for this study is threefold. First, it addresses the issue of reflective teaching, which has become a desirable approach for teachers professional evelopment. The second perspective is teachers interaction, considered by manyauthors as a powerful strategy to make these professionals aware of the educational possibilities of their practice. The third perspective deals with the contemporary trends in language teaching, in which the discussion about foreign language teaching in statecschools is situated. The findings showed that the process of reflection offered the teachers a better perception of their lessons, as their final descriptions included the consequences of theirpractice for the students. Moreover, various practical theories were revealed and discussed, generating consensual theories that are relevant to the debate about foreign language teaching in state schools. The reflections on the results of the teachinglearning process were very rich because the teachers not only self-criticized but also perceived the need to alter their pedagogical practice. Lastly, the interactive reflection promoted professional and theoretical changes. The theoretical changes concern the four categories: content, objectives, instructional procedures, and teacher. In brief, this research shows the importance for in-service teachers to have opportunities to reflect interactively about their own practice and the results of this practice, given that it has turned out to be highly effective for the professional development of the four participants.